2022
DOI: 10.3390/foods11040586
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Biodegradable κ-Carrageenan Based Anti-Bacterial Film Functionalized with Wells-Dawson Polyoxometalate

Abstract: In the present study, an anti-bacterial film (Carr/POM film) was prepared through the incorporation of Wells-Dawson polyoxometalate K6[Mo18O62P2] into κ-carrageenan-based polymers using the tape-casting method. The mechanical properties, thermal stability, and morphology of the prepared film were characterized. The obtained results showed that incorporation of K6[Mo18O62P2] significantly affected the morphology and structure of the films. Moreover, the polyoxometalate-based film demonstrated desirable bacteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 55 publications
3
7
0
Order By: Relevance
“…52 The third thermal decomposition phase appeared at 240−270 °C (maximum peak in the DTG curve), principally due to the thermal degradation of the carrageenan matrix. 51 A similar behavior has been reported in a previous study where κcarrageenan and a locust bean gum composite material were studied. 43 After the third degradation stage, all films confirmed a progressive reduction in weight up to 500 °C.…”
Section: Mechanical Attributessupporting
confidence: 81%
See 2 more Smart Citations
“…52 The third thermal decomposition phase appeared at 240−270 °C (maximum peak in the DTG curve), principally due to the thermal degradation of the carrageenan matrix. 51 A similar behavior has been reported in a previous study where κcarrageenan and a locust bean gum composite material were studied. 43 After the third degradation stage, all films confirmed a progressive reduction in weight up to 500 °C.…”
Section: Mechanical Attributessupporting
confidence: 81%
“…The inclusion of GFO in the films caused variation in the thermal stability of the films as presented by TGA, DSC, and DTG thermograms. All kappa carrageenan-based films showed several thermal decomposition regions as reported in previous studies . The initial thermal decomposition phase was found between 37 and 102 °C due to the hydrophilic nature of carrageenan, leading to water evaporation and chemisorbed water via hydrogen bonds.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…This study aims to evaluate the hydrate-inhibiting potential of Lambda-Carrageenan (λ-crgn), a natural, sustainable, biodegradable, and non-toxic polysaccharide. While the biodegradability of PVCap and PVP is less than 2% in 28 days. All different derivatives of carrageenan show very high biodegradability and have almost 90% degradation within 30 days. The study aimed to assess the performance of different variants of λ-crgn when used alone and when combined with different solvents, such as mono ethylene glycol (MEG) and 4-methyl-1-pentanol (4m1P), and with commonly used KHIs, such as polyvinylpyrrolidone (PVP) and Polyvinylcaprolactam (PVCap). Figure displays the structures of λ-crgn, the two solvents, and the two KHI polymers used in the study.…”
Section: Objectivementioning
confidence: 99%
“…It can be observed that κCHM-0 film had three obvious stages of thermal degradation. The first stage appeared at around 50 • C, representing the evaporation of water within the film matrix [43]. The second stage from 130.55 • C to 229.73 • C was caused by glycerol decomposition, and the third stage from 233.04 • C to 316.81 • C was ascribed to the κ-carrageenan decomposition.…”
Section: Thermal Stabilitymentioning
confidence: 99%